Maintenance of Rhodopsin levels in Drosophila photoreceptor and phototransduction requires Protein Kinase D. Issue 3 (2nd October 2018) - Ashe, Sudipta; Yadav, Shweta
ABSTRACT: During Drosophila phototransduction, the G protein coupled receptor (GPCR) Rhodopsin (Rh1) transduces photon absorption into electrical signal via G-protein coupled activation of phospholipase C (PLC). Rh1 levels in the plasma membrane are critical for normal sensitivity to light. In this study, we report that Protein Kinase D (dPKD) regulates Rh1 homeostasis in adult photoreceptors. Although eye development and retinal structure are unaffected in the dPKD hypomorph ( dPKD H ), it exhibited elevated levels of Rh1. Surprisingly, despite having elevated levels of Rh1, no defect was observed in the electrical response to light in these flies. By contrast the levels of another transmembrane protein of the photoreceptor plasma membrane, Transient receptor potential (TRP) was not altered in dPKD H . Our results indicate that dPKD is dispensable for eye development but is required for maintaining Rh1 levels in adult photoreceptors.